The Toys' s Party - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (UK Oxford university press, 2012)
Kipper wants to have a party for his toys. When Mum says no, Kipper decides to have the party anyway. He prepares food using strange ingredients like cornflakes, milk, jam, tomato sauce, and baked beans$1 (Ball mixed in a bowl! The party ends in a mess when Mum finds out and Kipper feels unwell from the unusual "party food."s
H3
4 to 6 years old, emerging readers beginning to decode simple CVC words (e.g., cat, dog, cup) Familiar with basic sight words (e.g., "the", "and", "to") Learning to read with context clues, illustrations, and repeated sentence structures
Keywords: Supplementary reading material